Innate C-H functionalization of cyclic enaminones - Yu, Yiyun (My University, 2013)
Cyclic enaminones are versatile precursors for the synthesis of alkaloids and nitrogen-containing bioactive compounds. The development of efficient functionalization methods is vital to their synthetic utility. C-H functionalization is a tool to efficiently construct C-C bonds with high atom-economy, and to reduced waste. The work in this dissertation is directed towards the development of efficient and selective C-H functionalization methods for cyclic enaminones.Chapter 1 serves as an introduction to cyclic enaminone chemistry. The synthesis and reactivity of cyclic enaminones, including applications in total synthesis, are summarized. In particular, our recent developments regarding enaminone chemistry are highlighted. Chapter 2 surveys recent advances in Pd-catalyzed C-H functionalization at sp2 carbons. The highlights and problems for C-H functionalization are discussed in detail.Chapter 3 describes a regioselective C-H arylation of cyclic enaminones with aryl iodides. The wide availability of aryl iodides allowed rapid access to 3-arylpiperidines. Chapter 4 expands the reaction scope of cyclic enaminones and presents a unique dehydrogenative alkenylation. This pioneering work is among the early examples of a C-H cross-coupling reaction between alkenes. A variety of cyclic enaminones and alkenes were employed. A mechanistic study of the C-H palladation is also included.Chapter 5 focuses on the synthesis of 5-alkenyluracil scaffolds of medicinal importance. A practical, high-yielding dehydrogenative alkenylation method is presented. The generality of this new method shows a significant improvement over past syntheses.Chapter 6 explores the synthetic utility of alkenylated cyclic enaminones. A superior dehydrogenative alkenylation reaction was discovered using a biomimetic approach. A tandem reaction was found serendipitously that led to a novel synthesis of chalcones.Chapter 7 documents progress concerning the C-H trifluoromethylation of cyclic enaminones. Existing protocols were examined and a palladium-catalyzed protocol was pursued. Remarkably, it was discovered that a metal-free protocol was similarly effective.Our efforts have afforded practical means to functionalize cyclic enaminones. These protocols will undoubtedly increase the synthetic value of cyclic enaminones.
University of Minnesota Ph.D. dissertation. August 2013. Major: Chemistry. Advisor: Gunda I. Georg. 1 computer file (PDF); xxii, 236 pages.
Keywords: Catalysis; C-H Activation; Enaminone; Heterocycle; Palladium; Synthetic Methodology